Methods of braking seed dormancy on germination and early seedling growth of African locust bean (Parkia biglobosa) (JACQ.) Benth - Okunlola, A. I.; Adebayo, R. A.; Orimogunje, A. D. (Global Journal of Food and Agribusiness Management, 2019)
An experiment was conducted under a net house in the department of Crop, Soil and Pest Management of the Federal University of Technology Akure. This was to investigate the most effective pre-sowing treatments to break seed dormancy, to stimulate seed germination and to identify morphological traits for the assessment of Parkia biglobosa seedling vigour. Matured seeds of P. biglobosa were collected from farmers in Akoko in Southwest Nigeria, dried at room temperature and tested for viability by floatation. The seeds were then subjected to pretreatment that includes: soaking in 100% sulphuric acid for one minute, mechanical scarification with sandpaper, soaking in boiling water for two minutes, soaking in cold water (at room temperature) for 24 h. At 12 weeks, the seedlings growth parameters were assessed: seedling height, leaf production, and diameter and branch production. Result obtained shows that all the treatments except soaking in boiling water improved seed germination and reduced Mean Germination Time (MGT). The mechanical scarification appeared to be the most effective method of pre-treatment having the highest germination percentage 91.7%. Plant height appeared to be the strongest morphological trait to identify vigorous seedlings of P. biglobosa. Higher value of plant heights, number of leaves, branches and stem girth were recorded on the seedlings treated with scarification while hot water treated seeds performed low. This study revealed that seeds mechanically scarified improved seed germination and seedling growth. It is therefore recommended that mechanical scarification of the seeds of P. biglobosa may be effective for breaking dormancy and improving the seedling vigour which can enhance the domestication and cultivation of these valuable seeds in the environment.